2008
DOI: 10.1177/1043659608322422
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the HIV/AIDS-Related Knowledge, Attitudes, and Behaviors of University Students in Botswana

Abstract: Substantive, methodological, and theoretical implications are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 3 publications
1
9
0
Order By: Relevance
“…The majority of students knew that the use of condoms during sexual intercourse could prevent HIV. Similar findings were reported by previous studies [10][11][12][13][14]12,18,19]. These misconceptions may increase the likelihood of HIV spread.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The majority of students knew that the use of condoms during sexual intercourse could prevent HIV. Similar findings were reported by previous studies [10][11][12][13][14]12,18,19]. These misconceptions may increase the likelihood of HIV spread.…”
Section: Discussionsupporting
confidence: 91%
“…Another study from Botswana, reported that Teachings at the University health center about diseases and health prevention were appreciated by the study groups that had used that facility. In addition to increasing knowledge, it also appeared that the HIV/AIDS course improved students' attitudes toward HIV-positive people and even helped them change certain behaviors (e.g., limiting partners, using condoms correctly, and being tested for HIV) [14]. Although HIV/AIDS-related KAPs are reported in studies from other countries, there was no such information for school students in Libreville Gabon.…”
Section: The Aids Epidemic In Gabonmentioning
confidence: 99%
“…In the Southern African Region, there are several examples of curriculum interventions and courses offered on HIV/AIDS education, such as at the University of Botswana (Brown et al 2008). Also, at the University of Witwatersrand, South Africa, HIV/AIDS education has been incorporated into academic curricula (Cairns, Dickinson, and Orr 2006).…”
Section: Research Focusmentioning
confidence: 98%
“…Two recent follow-up studies using student focus groups found continued perceptions that these high-risk sexual behaviors were common among University of Botswana students, but recent quantitative data are lacking (Brown et al, 2008; Sabone et al, 2007). Given this, the goals of the current study were twofold: to quantitatively examine the knowledge, attitudes, and sexual practices in relation to HIV-1 prevention among University of Botswana students, a highly educated group of at-risk young adults, and to document the attitudes and beliefs of these students around HIV testing and condom use.…”
Section: Introductionmentioning
confidence: 99%